Efektivitas Terapi Zikir Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi - Ricky Zainuddin; Ekayanti Hafidah Ahmad; Syahruni Syahruni; Yantimala Mahmud; Nurbaiti Nurbaiti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Zikir therapy is one way to approach God that aims to find peace of mind and peace of mind. Purpose: By doing zikir will suppress the work of the sympathetic nervous system and activate the work of the parasympathetic nervous system so that it will make someone feel calm. Method: This research explores evidence published in Google Scholar electronic data. Using a search strategy, we obtained 34 potential and relevant articles, from 34 articles of two studies included in the final analysis. Results: We were able to see a significant effect in reducing blood pressure after patients were given zikir therapy. Conclusion: From these results it can be concluded that zikir therapy is a non-pharmacological therapy that can reduce blood pressure in hypertensive sufferers. Health workers can participate in providing this therapy.